Determination of the Relationship between Individuals’ Attitudes towards the COVID-19 Vaccine and Their Level of Fear - Kavaklı, Hilal; YALÇINÖZ BAYSAL, HASRET (Advances in Nursing & Midwifery, 2024)
Introduction: In order to achieve success in the fight against the pandemic, society’s perception of the pandemic and its attitudes towards its control have gained importance. It is wondered whether the level of fear experienced during the pandemic affects individuals’ attitudes towards the COVID-19 vaccine. The purpose of this study is to determine the relationship between individuals’ attitudes towards the COVID-19 vaccine and their level of fear. Methods: This study utilized a descriptive and correlational design. The sample of the study consisted of 400 individuals aged 18-70 years who lived in Erzurum city center in Turkey between May 2021 and January 2023 and agreed to participate in the study. Data were collected through the Personal Information Form, the Fear of COVID-19 Scale, and the Attitudes towards the COVID-19 Vaccine Scale. Ethics committee approval was obtained for the study. Data analysis was done in a computer environment using SPSS 20 package program and parametric tests were used. Results: It was determined that the average age of the participants was 33.87±14.93, 66.3% were female, 34.7% had a bachelor’s degree or higher, 53.2% were single, 71.8% were unemployed, 57% lived with their families, 71.8% did not smoke, and 84.3% did not have a chronic disease. The Attitudes towards the COVID-19 Vaccine Scale positive attitude sub-scale mean score was 3.41±1.41 and the negative attitude sub-scale mean score was 3.28±1.15. It was determined that the total score average obtained from the Fear of COVID-19 Scale was 17.42±8.70, indicating above-average fear. A positive and moderate-level correlation was detected between the participants’ Attitudes towards the COVID-19 Vaccine Scale positive and negative attitude sub-scales and the fear of COVID-19 scores (r= 0.582, p<0.001). Conclusions: The results obtained show that the participants’ attitudes towards the COVID-19 vaccine are positive. Fear of COVID-19 positively affects attitudes towards vaccines.